Women’s Agency in Micro Enterprises and Strategies for Family Economic Survival - Milyan Milyan; Sitti Rahmatyah; Yunila Yunila (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Women play a vital role in sustaining family economies, particularly in the micro-business sector. The COVID-19 pandemic has increased economic vulnerability, pushing many women into informal businesses as a survival strategy. However, women's agency in managing micro-enterprises remains understudied, especially in the context of socio-cultural constraints in developing countries like Indonesia. Objectives: This study aims to explore the experiences of women micro-entrepreneurs in managing businesses, making financial decisions, and adapting to market challenges. It focuses on how women exercise agency within family and community dynamics while navigating the informal economy. Methods: A qualitative narrative approach was employed. Data were collected through in-depth interviews with five women micro-entrepreneurs in the ICP area. Thematic analysis was conducted to identify patterns of agency, adaptation strategies, and barriers faced by the participants. Results: Findings reveal that women perceive their roles as both primary breadwinners and supporters of family income. Most participants manage daily earnings by allocating funds for capital, savings, and household needs. Challenges include market competition and unpredictable weather affecting sales. Several participants adapted by using social media for marketing. The level of financial control varies, with some women fully autonomous while others share decision-making with their husbands. Conclusion: Women in micro-enterprises demonstrate resilience and agency in sustaining family livelihoods. However, structural and cultural barriers still influence their roles and decision-making autonomy.